Identification of Genes Related to Nitrogen Uptake in Wine Strains of Saccharomyces Cerevisiae - Contreras-Opazo, A; Martinez-Fernandez, C; Ganga-Munoz, M; Garcia-Mena, V; Salinas-Sanhueza, F (2012)
The yeast Saccharomyces cerevisiae is the main microorganism responsible for wine fermentation and its development influences the quality of wine. A problem affecting these types of fermentations, generating important losses in this industry, are the slow or stuck fermentations which may result from low nitrogen availability in the must. Therefore, several studies have been directed towards identifying genes involved in nitrogen metabolism using high throughput strategies which include subjecting the yeast to changes in the type or concentration of the available nitrogen source. However, this type of approach can also generate responses in the yeast that do not necessarily alter the expression of genes related to nitrogen metabolism. In this work, by using intraspecific hybridisation of wild wine yeast strains we obtained genetically and oenologically similar strains with differences in the consumption of nitrogen sources. Using the same must, the global expression patterns of these yeasts were compared by microarrays, the analysis of which identified 276 genes that varied in their expression between the strains analysed. The functional analysis of the genes with a known function indicates that some participate in nitrogen metabolism, alcoholic fermentation, ion transport and transcriptional regulation. Furthermore, differences were observed in the expression of genes which have been partially associated to nitrogen, as in the case of ZRT1 and ATO2. Interestingly, many of the genes identified have no known function or have not been previously associated to this phenotype. © 2011 Springer Science+Business Media B.V.